2020
DOI: 10.3389/feart.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes to Extreme Runoff and Precipitation Events From a Downscaled Simulation Over the Western United States

Abstract: Extreme precipitation and runoff events, which often impact natural and social systems more than mean changes, generally occur over regional scales. Future climate projections can be used to estimate how the hydrologic cycle may change, but the coarse resolution of global climate models (GCMs) (>1 •) makes it difficult to evaluate regional changes, such as over a single watershed. To estimate changes in hydroclimatic variables at finer spatial resolutions, we dynamically downscale the Community Climate System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 96 publications
3
13
0
Order By: Relevance
“…Our future projections of WAFR provide clear evidence that increases in high-magnitude-flows are highly likely under climate change in California ( Fig. 1 ), as supported by previous studies reporting substantial and robust increases in projected extreme precipitation ( 23 , 31 ) and streamflow ( 16 , 19 , 20 ). Earlier snowmelt and larger increases in rain-on-snow events also contribute to more extreme streamflow ( 32 ), implying higher WAFR under climate change.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our future projections of WAFR provide clear evidence that increases in high-magnitude-flows are highly likely under climate change in California ( Fig. 1 ), as supported by previous studies reporting substantial and robust increases in projected extreme precipitation ( 23 , 31 ) and streamflow ( 16 , 19 , 20 ). Earlier snowmelt and larger increases in rain-on-snow events also contribute to more extreme streamflow ( 32 ), implying higher WAFR under climate change.…”
Section: Discussionsupporting
confidence: 84%
“…The largest robust increases are concentrated over WAFR-abundant Northern California, including the Sacramento River and North Coast hydrologic regions. These findings are in line with previous research (19,20), which also found substantial and widespread increases in highmagnitude-flow events, especially for basins in the northern and central Sierra Nevada. In contrast, there is almost no increase (and in some cases, even a decrease) in the WAFR-limited dry Southern California (Fig.…”
Section: Historical and Future Estimates Of Maximum Wafrsupporting
confidence: 93%
“…In this study, we explored how our management of the well-known errors and biases in coupled land-atmosphere modeling systems (e.g., WRF-Noah-MP) used to simulate current hydrology (as in this study) and increasingly to project regional climate change impacts (Huang et al 2018;Musselman et al 2018;Schwartz et al 2017;Wrzesien and Pavelsky 2020) can strongly distort our perceptions of vulnerabilities in institutionally complex major global water resources systems such as the north-central California case analyzed in this study. We show how streamflow errors from an atmospheric and land-surface hydrologic model, WRF-Noah-MP, propagate into a water management model, CALFEWS, and affect perceptions of systemwide water supplies, groundwater banking, and the annual revenue of irrigation districts.…”
Section: Discussionmentioning
confidence: 99%
“…Future climate change studies predict not only warming temperatures in many geographic areas, but also an increasing number of extreme events [36]. Rainfall and snow may be especially susceptible to change towards more extremes in the Sierra Nevada Mountain range [37][38][39] and, thus, have strong impacts on the business of TNC in the future-affecting the companies, the individual drivers, as well as customers taking rides.…”
Section: Discussionmentioning
confidence: 99%